ECONOMIC ASSESSMENT OF LAND RESOURCES (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article analyzes rent and its economic essence. Explains land rent and its economic significance, valuation methods. The article discusses theoretical and methodological issues and methodological approaches to the economic assessment of land resources.